Electrochemical Devices

The electrochemical device balances high capacity and durability by optimizing the positive to negative electrode active material ratio and incorporating a lithium carbonate and SEI film surface layer, enhancing performance and stability.

JP7620854B2Active Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022530085
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-09
Filing Date
2021-05-18
Publication Date
2025-01-24
Estimated Expiration
2041-05-18

AI Technical Summary

Technical Problem

Existing electrochemical devices face a trade-off between high capacity and high durability, making it difficult to achieve a balanced performance.

Method used

The electrochemical device is designed with a specific ratio of positive and negative electrode active materials (MP/MN ratio of 1.1 to 2.5) and includes a surface layer on the negative electrode comprising a first layer of lithium carbonate and a second layer of a solid electrolyte interface film (SEI film) to enhance performance.

Benefits of technology

This configuration achieves a high capacity while maintaining low resistance and durability, with the MP/MN ratio of 1.4 to 1.8 providing optimal balance and the surface layer stabilizing the SEI film for improved performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620854000003
    Figure 0007620854000003
  • Figure 0007620854000001
    Figure 0007620854000001
  • Figure 0007620854000002
    Figure 0007620854000002
Patent Text Reader

Abstract

The present invention provides an electrochemical device which has both high capacity and high durability. This electrochemical device comprises a positive electrode, a negative electrode and a lithium ion-conductive electrolyte; the positive electrode is provided with a positive electrode collector and a positive electrode mixture layer that is supported by the positive electrode collector; the positive electrode mixture layer contains a positive electrode active material that is reversibly doped with anions; the negative electrode is provided with a negative electrode collector and a negative electrode mixture layer that is supported by the negative electrode collector; the negative electrode mixture layer contains a negative electrode active material that is reversibly doped with lithium ions; the negative electrode active material contains hardly-graphitizable carbon; and the ratio of the mass Mp of the positive electrode active material supported by unit area of the positive electrode to the mass Mn of the negative electrode active material supported by unit area of the negative electrode, namely Mp / Mn is from 1.1 to 2.5.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to electrochemical devices. [Background technology]

[0002] In recent years, electrochemical devices that combine the power storage principles of lithium ion secondary batteries and electric double layer capacitors have been attracting attention. Such electrochemical devices usually use a polarizable electrode as the positive electrode and a non-polarizable electrode as the negative electrode. As a result, electrochemical devices are expected to combine the high energy density of lithium ion secondary batteries with the high output characteristics of electric double layer capacitors.

[0003] Patent Document 1 describes a lithium ion capacitor comprising a positive electrode, a negative electrode, and an aprotic organic solvent electrolyte solution of a lithium salt as an electrolyte, in which the positive electrode active material is a material capable of doping and dedoping lithium ions and / or anions, the negative electrode active material is a material capable of doping and dedoping lithium ions, the negative electrode and / or the positive electrode are doped with lithium ions so that the potential of the positive electrode after short-circuiting the positive electrode and the negative electrode is 2 V (vs. Li / Li+) or less, the positive electrode layer in the positive electrode is formed with the same thickness on both sides of the current collector, the total thickness of the positive electrode layer is 18 to 108 μm, and the total basis weight of the positive electrode active material is 1.5 to 4.0 mg / cm 2 The present invention proposes a lithium ion capacitor characterized by:

[0004] Patent Document 2 proposes a lithium ion capacitor comprising a positive electrode, a negative electrode, and an aprotic organic solvent electrolyte solution of a lithium salt as an electrolyte, in which the positive electrode active material is a material capable of reversibly supporting lithium ions and / or anions, the negative electrode active material is a material capable of reversibly supporting lithium ions, lithium ions are doped into the negative electrode and / or positive electrode before charging so that the potential of the positive electrode after the positive electrode and negative electrode are short-circuited is 2.0 V or less, and the negative electrode active material is a heat-treated product of a carbon material precursor in the presence of a transition metal-containing substance.

[0005] Patent Document 3 proposes an electrochemical capacitor that includes an element composed of a negative electrode in which a negative electrode layer containing a carbon material in which lithium ions are occluded is formed on the surface of a current collector, a positive electrode in which a positive electrode layer that adsorbs ions is formed on the surface of a current collector, and a separator interposed between the negative electrode and the positive electrode, an electrolyte containing lithium ions, and an exterior body that contains the element and the electrolyte, and in which a coating containing lithium carbonate is formed on the surface of the carbon material contained in the negative electrode layer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 4971729 [Patent Document 2] JP 2006-310412 A [Patent Document 3] International Publication No. 2011 / 58748 Summary of the Invention

[0007] However, in the electrochemical devices described above, high capacity and high durability are in a trade-off relationship that is difficult to achieve at the same time, and further improvements are required.

[0008] One aspect of the present invention includes a positive electrode, a negative electrode, and a lithium ion conductive electrolyte, the positive electrode including a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector, the positive electrode mixture layer including a positive electrode active material that is reversibly doped with anions, the negative electrode including a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer including a negative electrode active material that is reversibly doped with lithium ions, and the negative electrode active material including non-graphitizable carbon. ,before The mass Mn of the negative electrode active material supported per unit area of ​​the negative electrode The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode The ratio of Mp / Mn is 1.1 or more and 2.5 or less.

[0009] According to the present invention, it is possible to provide an electrochemical device that has both high capacity and high durability. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a partially cutaway perspective view of an electrochemical device according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The electrochemical device according to the embodiment of the present invention includes a positive electrode, a negative electrode, and a lithium ion conductive electrolyte. In general, the positive electrode and the negative electrode constitute an electrode body together with a separator interposed therebetween. The electrode body is formed, for example, as a columnar wound body by winding a strip-shaped positive electrode and a negative electrode with a separator interposed therebetween. The electrode body may also be formed as a laminate by stacking a plate-shaped positive electrode and a plate-shaped negative electrode with a separator interposed therebetween.

[0012] The positive electrode comprises a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector. The positive electrode mixture layer contains a positive electrode active material that reversibly dopes anions. When anions are adsorbed to the positive electrode active material, an electric double layer is formed, and capacitance is generated. The positive electrode may be a polarizable electrode, or may be an electrode that has the properties of a polarizable electrode and also contributes to the capacitance through a Faraday reaction.

[0013] The positive electrode active material may be a carbon material or a conductive polymer. The doping of the positive electrode active material with an anion includes at least the adsorption phenomenon of the anion to the positive electrode active material, and may also include the occlusion of the anion by the positive electrode active material and the chemical interaction between the positive electrode active material and the anion.

[0014] The negative electrode includes a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector. The negative electrode mixture layer includes a negative electrode active material that reversibly dopes lithium ions, and the negative electrode active material includes non-graphitizable carbon.

[0015] The non-graphitizable carbon develops capacity by undergoing a Faraday reaction in which lithium ions are reversibly absorbed and released. The doping of lithium ions into the negative electrode active material is a concept that includes at least the absorption phenomenon of lithium ions into the negative electrode active material, and may also include the adsorption of lithium ions into the negative electrode active material and chemical interaction between the negative electrode active material and lithium ions.

[0016] Hereinafter, the positive electrode and the negative electrode may be collectively referred to as electrodes. The positive electrode current collector and the negative electrode current collector may be collectively referred to as current collectors (or electrode current collectors). The positive electrode mixture layer and the negative electrode mixture layer may be collectively referred to as mixture layers (or electrode mixture layers). The positive electrode active material and the negative electrode active material may be collectively referred to as active materials (or electrode active materials).

[0017] negative Mass of negative electrode active material supported per unit area of ​​electrode, Mn Mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode The ratio of Mp / Mn is 1.1 or more and 2.5 or less, preferably 1.4 or more and 1.8 or less, more preferably 1.5 or more and 1.8 or less. The electrochemical device having the above Mp / Mn ratio can achieve a high capacity. When the Mp / Mn ratio is less than 1.1, the capacitance of the electrochemical device decreases significantly. On the other hand, when the Mp / Mn ratio is 1.1 or more, further 1.4 or more, particularly 1.5 or more, a high capacitance can be obtained. However, when the Mp / Mn ratio exceeds 2.5, the resistance (DCR) at low temperature (hereinafter referred to as low-temperature DCR) of the electrochemical device increases excessively. On the other hand, when the Mp / Mn ratio is 2.5 or less, further 1.8 or less, a high capacitance can be obtained and an excessive increase in the low-temperature DCR can be suppressed, and an electrochemical device with excellent balance of characteristics can be obtained.

[0018] The mass Mp and mass Mn of the electrode active material supported per unit area of ​​the electrode are respectively expressed by the following formulas.

[0019] Mp = (mass of positive electrode - mass of positive electrode current collector) x mass ratio of positive electrode active material ÷ area of ​​positive electrode

[0020] Mn = (Mass of negative electrode - Mass of negative electrode current collector) x Mass ratio of negative electrode active material ÷ Area of ​​negative electrode

[0021] Here, the mass ratio of the positive electrode active material is the ratio of the mass of the positive electrode active material contained in the positive electrode mixture layer when the mass of the positive electrode mixture layer is set to 1. Similarly, the mass ratio of the negative electrode active material is the ratio of the mass of the negative electrode active material contained in the negative electrode mixture layer when the mass of the negative electrode mixture layer is set to 1. In addition, the positive electrode area is the area of ​​the projection of the positive electrode when projected orthogonally from the main surface side of the positive electrode, and the negative electrode area is the area of ​​the projection of the negative electrode when projected orthogonally from the main surface side of the negative electrode.

[0022] In addition, as the samples of the positive electrode and the negative electrode for determining Mp and Mn, uniform portions are cut out from the electrodes in the thickness direction of the electrodes. For example, the electrode portion having a partially exposed portion of the current collector is not used as the sample. In addition, the electrode portion having a mixture of portions in which the electrode mixture layer is provided on both sides and one side of the current collector is not used as the sample.

[0023] From the viewpoint of obtaining an electrochemical device with high capacity density, the mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is, for example, 3.6 mg / cm 2 More than 4.5mg / cm 2 It is sufficient if it is less than 3.9 mg / cm 2 More than 4.2mg / cm 2 From the same viewpoint, the mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode may be, for example, 1.8 mg / cm 2 More than 3.2mg / cm 2 It is sufficient if it is less than 2.3 mg / cm 2 Above 2.8mg / cm 2 When an electrode mixture layer is provided on both sides of a current collector, the mass of the active material supported on a unit area of ​​the electrode is calculated from the total amount of the active material on both sides of the current collector having the size of the unit area, as derived from the above definition of the electrode area.

[0024] Next, the specific surface area of ​​the negative electrode mixture layer is, for example, 10 m 2 / g or more, 70m2 The lower the specific surface area of ​​the negative electrode mixture layer, the greater the DCR. 2 / g or more, even 25m 2 / g or more, the increase in low-temperature DCR is significantly suppressed. 2 / g or more, even 25m 2 By setting the specific surface area of ​​the negative electrode mixture layer to 70 m or more, it becomes easier to select a large Mp / Mn ratio, and it becomes easier to achieve a high electrostatic capacity. 2 / g or less, and even 50m 2 / g or less, the deterioration of the negative electrode is suppressed, and the durability of the electrochemical device is easily improved. Here, the deterioration of the negative electrode can typically be evaluated by the rate of increase in the low-temperature DCR of the electrochemical device when float charging is performed at high temperature, in which a constant voltage is applied to the electrochemical device using an external DC power source. The rate of increase in low-temperature DCR is the ratio of the difference (ΔDCR) between the initial low-temperature DCR and the low-temperature DCR after float charging to the initial low-temperature DCR of the electrochemical device. It can be said that the smaller the rate of increase in low-temperature DCR, the smaller the deterioration of the negative electrode.

[0025] The specific surface area of ​​the negative electrode mixture layer is the BET specific surface area determined using a measuring device conforming to JIS Z8830 (e.g., Tristar II3020 manufactured by Shimadzu Corporation). Specifically, the electrochemical device is disassembled, and the negative electrode is taken out. A half cell is assembled using this negative electrode as the working electrode and Li metal foil as the counter electrode, and Li in the negative electrode is de-doped until the negative electrode potential becomes 1.5 V. Next, the negative electrode from which Li has been de-doped is washed with dimethyl carbonate (DMC) and dried. Thereafter, the negative electrode mixture layer is peeled off from the negative electrode current collector, and about 0.5 g of a sample of the negative electrode mixture layer is taken.

[0026] Next, the collected sample is heated at 150°C for 12 hours under a reduced pressure of 95 kPa or less, and then nitrogen gas is adsorbed onto a sample with a known mass to obtain an adsorption isotherm in the range of relative pressures from 0 to 1. The surface area of ​​the sample is then calculated from the monolayer adsorption amount of the gas obtained from the adsorption isotherm. Here, the specific surface area is calculated from the following BET formula using the BET single-point method (relative pressure 0.3).

[0027] P / V(P0-P)=(1 / VmC)+{(C-1) / VmC}(P / P0)...(1)

[0028] S = kVm (2)

[0029] P0: Saturated vapor pressure P: Adsorption equilibrium pressure V: Amount of adsorption at the adsorption equilibrium pressure P Vm: Monolayer adsorption amount C: Parameters related to heat of adsorption, etc. S: Specific surface area k: Nitrogen monomolecular area 0.162 nm 2

[0030] Next, the surface layer portion of the negative electrode mixture layer may have a first layer containing lithium carbonate as a coating component. The first layer is formed mainly on the surface of the negative electrode active material. The larger the specific surface area of ​​the negative electrode mixture layer, the more likely the negative electrode is to deteriorate, but by forming the first layer, the deterioration of the negative electrode is significantly suppressed.

[0031] The surface portion of the negative electrode may have a second layer containing a solid electrolyte as a component of the coating. The second layer has a different composition from the first layer, and the second layer is distinguishable from the first layer. In an electrochemical device using lithium ions, a solid electrolyte interfacial coating (i.e., SEI coating) is formed on the negative electrode mixture layer during charging and discharging. The second layer may be formed as an SEI coating. The SEI coating plays an important role in the charge and discharge reaction, but if the SEI coating is formed excessively thick, the deterioration of the negative electrode increases. In contrast, the first layer containing lithium carbonate has the effect of promoting the formation of a good SEI coating and maintaining the SEI coating in a good state when charging and discharging are repeated. Therefore, by forming the first layer on the surface portion of the negative electrode mixture layer, the deterioration of the negative electrode can be significantly suppressed even when the specific surface area of ​​the negative electrode mixture layer is increased to suppress an increase in low-temperature DCR.

[0032] When the coating has a first layer and a second layer, at least a part of the second layer covers at least a part of the surface of the negative electrode active material via the first layer. That is, at least a part of the first layer is covered by the second layer. The first layer is interposed between the surface of the negative electrode active material and the second layer, and serves as a base layer for the second layer. The first layer serves as a base layer, and thus the second layer is formed as a good condition SEI coating.

[0033] The second layer may also contain lithium carbonate. When the second layer contains lithium carbonate, the content of lithium carbonate in the second layer is less than the content of lithium carbonate in the first layer. The first layer, which contains a large amount of lithium carbonate, is used as the base layer, which is a necessary condition for the second layer to be formed as a good SEI coating.

[0034] The first layer is formed on the surface of the negative electrode mixture layer before assembling the electrochemical device. In an electrochemical device assembled using the negative electrode, a homogeneous second layer (SEI film) of appropriate thickness is formed on the surface of the negative electrode active material by subsequent charging and discharging. The SEI film is formed, for example, by a reaction between an electrolyte and a negative electrode in an electrochemical device. Since the electrolyte can pass through not only the second layer but also the first layer, the entire surface including the first and second layers may be referred to as the SEI film, but in this specification, for convenience, the second layer is referred to as the SEI film and is distinguished from the first layer.

[0035] The presence of a region containing lithium carbonate such as the first layer can be confirmed by, for example, analyzing the surface layer by X-ray photoelectron spectroscopy (XPS), although the analysis method is not limited to XPS.

[0036] The thickness of the first layer may be, for example, 1 nm or more, and may be 5 nm or more if a longer-term effect is expected, and may be 10 nm or more if a more reliable effect is expected. However, if the thickness of the first layer exceeds 50 nm, the first layer itself may become a resistance component. Therefore, the thickness of the first layer may be 50 nm or less, or may be 30 nm or less.

[0037] The thickness of the second layer may be, for example, 1 nm or more, may be 3 nm or more, and 5 nm or more is sufficient. However, if the thickness of the second layer exceeds 20 nm, the second layer itself may become a resistance component. Therefore, the thickness of the second layer may be 20 nm or less, or may be 10 nm or less.

[0038] The ratio A / B of the thickness A of the first layer to the thickness B of the second layer is preferably 1 or less from the viewpoint of reducing the initial low-temperature DCR. In this case, the thickness of the second layer is preferably 20 nm or less, and may be 10 nm or less. However, from the viewpoint of forming a second layer in good condition, it is desirable that A / B is 0.1 or more, and for example, the A / B ratio may be 0.2 or more.

[0039] The thicknesses of the first layer and the second layer are measured by analyzing the surface portion of the negative electrode mixture layer at multiple locations (at least 5 locations). The average of the thicknesses of the first layer or the second layer obtained at the multiple locations may be taken as the thickness of the first layer or the second layer. The negative electrode mixture layer to be used as the measurement sample may be peeled off from the negative electrode current collector. In this case, the coating formed on the surface of the negative electrode active material constituting the vicinity of the surface portion of the negative electrode mixture layer may be analyzed. Specifically, the negative electrode active material covered with the coating may be collected from the region of the negative electrode mixture layer disposed on the side opposite to the surface bonded to the negative electrode current collector and used for analysis.

[0040] For example, the XPS analysis of the surface portion of the negative electrode mixture layer is performed by irradiating an argon beam onto the surface portion or the coating formed on the surface of the negative electrode active material in the chamber of an X-ray photoelectron spectrometer, and observing and recording the changes in the spectra attributable to C1s, O1s electrons, etc. versus the irradiation time. In this case, the spectrum of the outermost surface of the surface portion may be ignored in order to avoid analytical errors. The thickness of the region where the peaks attributable to lithium carbonate are stably observed corresponds to the thickness of the first layer.

[0041] In the case of a negative electrode that has been completed and removed from an electrochemical device that has been subjected to a predetermined aging or at least one charge / discharge, the surface portion of the negative electrode mixture layer has an SEI coating (i.e., the second layer) containing a solid electrolyte. The thickness of the region where a peak attributable to the bond of the compound contained in the SEI coating is stably observed corresponds to the thickness of the SEI coating (i.e., the thickness of the second layer).

[0042] As the compound contained in the SEI coating, a compound containing an element that can be a label for the second layer is selected. As the element that can be a label for the second layer, for example, an element (e.g., F) that is contained in the electrolyte and is not substantially contained in the first layer may be selected. As the compound containing an element that can be a label for the second layer, LiF may be selected, for example.

[0043] When the second layer contains LiF, a substantial F1s peak attributable to LiF bonds is observed when the second layer is measured by X-ray photoelectron spectroscopy. In this case, the thickness of the region where the peak attributable to LiF bonds is stably observed corresponds to the thickness of the second layer.

[0044] On the other hand, the first layer does not usually contain LiF, and when the first layer is measured by X-ray photoelectron spectroscopy, a substantial F1s peak attributable to LiF bonds is not observed. Therefore, the thickness of the region where the peak attributable to LiF bonds is not stably observed may be taken as the thickness of the first layer.

[0045] An O1s peak attributed to lithium carbonate may also be observed in the SEI coating. However, the SEI coating formed in the electrochemical device has a different composition from the first layer formed in advance, so the two can be distinguished. For example, in an XPS analysis of the SEI coating, an F1s peak attributed to LiF bonds is observed, but a substantial F1s peak attributed to LiF bonds is not observed in the first layer. Furthermore, the amount of lithium carbonate contained in the SEI coating is small. As the Li1s peak, peaks derived from compounds such as ROCO2Li and ROLi may be detected.

[0046] When the first layer is analyzed by XPS, in addition to a first peak of O1s attributed to a C=O bond, a second peak of O1s attributed to a Li-O bond may be observed. The region of the coating present near the surface of the negative electrode active material may contain a small amount of LiOH or Li2O.

[0047] Specifically, when the first layer constituting the surface layer portion of the negative electrode mixture layer is analyzed in the depth direction, a first region in which a first peak (O1s attributed to a C=O bond) and a second peak (O1s attributed to a Li-O bond) are observed and the first peak intensity is greater than the second peak intensity, and a second region in which the first peak and the second peak are observed and the second peak intensity is greater than the first peak intensity may be observed in the order of increasing distance from the outermost surface of the surface layer portion. In addition, a third region may be further present that is closer to the outermost surface of the surface layer portion than the first region, and in which the first peak is observed but the second peak is not observed. The third region is easily observed when the thickness of the lithium carbonate-containing region is large.

[0048] The magnitude of the peak intensity may be determined based on the height of the peak from the baseline.

[0049] At the center of the first layer in the thickness direction, the C1s peak assigned to a CC bond is usually not substantially observed, or even if it is observed, its intensity is less than half of the peak intensity assigned to a C=O bond.

[0050] Next, a method for forming the first layer containing lithium carbonate on the surface layer of the negative electrode mixture layer will be described. The step of forming the first layer can be carried out by, for example, a gas phase method, a coating method, a transfer method, or the like.

[0051] Examples of the gas phase method include chemical vapor deposition, physical vapor deposition, and sputtering. For example, lithium carbonate may be deposited on the surface of the negative electrode mixture layer using a vacuum deposition device. The pressure in the chamber of the device during deposition is, for example, 10 -2 ~10 -5 Pa, the temperature of the lithium carbonate evaporation source may be 400 to 600°C, and the temperature of the negative electrode mixture layer may be -20 to 80°C.

[0052] As a coating method, a solution or dispersion containing lithium carbonate can be applied to the surface of the negative electrode using, for example, a microgravure coater, and then dried to form the first layer. The lithium carbonate content in the solution or dispersion is, for example, 0.3 to 2 mass %, and when a solution is used, the concentration may be equal to or lower than the solubility (for example, about 0.9 to 1.3 mass % in the case of an aqueous solution at room temperature).

[0053] Furthermore, a step of forming a second layer containing a solid electrolyte so as to cover at least a part of the first layer is performed to obtain a negative electrode. The surface layer portion of the obtained negative electrode mixture layer has a first layer and a second layer. The second layer is formed so that at least a part of it covers at least a part (preferably the entirety) of the surface of the negative electrode active material via the first layer (i.e., the first layer serves as a base layer).

[0054] The step of forming the second layer is performed in a state where the negative electrode mixture layer is in contact with the electrolyte, and therefore may also serve as at least a part of a step of pre-doping the negative electrode mixture layer with lithium ions. For example, metallic lithium may be used as a source of the pre-doped lithium ions.

[0055] Metallic lithium may be attached to the surface of the negative electrode mixture layer. In addition, a first layer containing lithium carbonate having a thickness of, for example, 1 nm or more and 50 nm or less can be formed by exposing a negative electrode having a negative electrode mixture layer to a carbon dioxide gas atmosphere.

[0056] The step of attaching metallic lithium to the surface of the negative electrode mixture layer can be carried out by, for example, a gas phase method, transfer, or the like. Examples of the gas phase method include chemical vapor deposition, physical vapor deposition, and sputtering. For example, metallic lithium may be formed in a film form on the surface of the negative electrode mixture layer by a vacuum deposition device. The pressure in the chamber of the device during deposition is, for example, 10 -2 ~10 -5 Pa, the temperature of the lithium evaporation source may be 400 to 600°C, and the temperature of the negative electrode mixture layer may be -20 to 80°C.

[0057] The carbon dioxide gas atmosphere is preferably a dry atmosphere that does not contain moisture, and may have a dew point of, for example, -40°C or lower or -50°C or lower. The carbon dioxide gas atmosphere may contain gases other than carbon dioxide, but the molar fraction of carbon dioxide is preferably 80% or higher, and more preferably 95% or higher. It is preferable that the atmosphere does not contain any oxidizing gas, and the molar fraction of oxygen is 0.1% or lower.

[0058] To form a thicker first layer, the partial pressure of carbon dioxide should be increased to, for example, 0.5 atm (5.05×10 4 Pa), it is more efficient to have a pressure of 1 atm (1.01×10 5 Pa) or more.

[0059] The temperature of the negative electrode exposed to the carbon dioxide gas atmosphere may be in the range of, for example, 15° C. to 120° C. The higher the temperature, the thicker the first layer becomes.

[0060] The thickness of the first layer can be easily controlled by changing the time for which the negative electrode is exposed to the carbon dioxide gas atmosphere. The exposure time may be, for example, 12 hours or more and less than 10 days.

[0061] The step of forming the first layer is preferably performed before constructing the electrode body, but may be performed after constructing the electrode body. That is, a positive electrode may be prepared, a negative electrode having a negative electrode mixture layer to which metallic lithium is attached may be prepared, a separator may be interposed between the positive electrode and the negative electrode to form an electrode body, and the electrode body may be exposed to a carbon dioxide gas atmosphere to form the first layer on the surface portion of the negative electrode mixture layer.

[0062] The pre-doping process of lithium ions into the negative electrode mixture layer is, for example, then further advanced by contacting the negative electrode mixture layer with an electrolyte, and is completed by leaving it for a predetermined time. Such a process may be a process of forming a second layer so as to cover at least a part of the first layer. For example, by performing at least one charge and discharge on the electrochemical device, the second layer can be formed on the negative electrode mixture layer and the pre-doping of lithium ions into the negative electrode can be completed. In addition, for example, the pre-doping of lithium ions into the negative electrode can also be completed by applying a predetermined charging voltage (for example, 3.4 to 4.0 V) between the terminals of the positive electrode and the negative electrode for a predetermined time (for example, 1 to 75 hours).

[0063] FIG. 1 is a schematic diagram showing the configuration of an electrochemical device 200 according to an embodiment of the present invention. The electrochemical device 200 includes an electrode assembly 100, a non-aqueous electrolyte (not shown), a metal cell case 210 with a bottom that accommodates the electrode assembly 100 and the non-aqueous electrolyte, and a sealing plate 220 that seals the opening of the cell case 210. A gasket 221 is disposed on the periphery of the sealing plate 220, and the inside of the cell case 210 is sealed by crimping the opening end of the cell case 210 to the gasket 221. A positive electrode current collector 13 having a through hole 13h in the center is welded to a positive electrode current collector exposed portion 11x. One end of a tab lead 15 connected to the positive electrode current collector 13 is connected to the inner surface of the sealing plate 220 at the other end. Thus, the sealing plate 220 functions as an external positive electrode terminal. On the other hand, a negative electrode current collector 23 is welded to a negative electrode current collector exposed portion 21x. The negative electrode current collector 23 is directly welded to a welding member provided on the inner bottom surface of the cell case 210. Therefore, the cell case 210 functions as an external negative electrode terminal.

[0064] Each of the components of the electrochemical device according to the embodiment of the present invention will now be described in more detail.

[0065] (Negative electrode) The negative electrode comprises a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer contains a negative electrode active material that reversibly dopes lithium ions, and the negative electrode active material contains non-graphitizable carbon (i.e., hard carbon). The thickness of the negative electrode mixture layer is, for example, 10 to 300 μm per side of the negative electrode current collector.

[0066] The negative electrode current collector is made of a sheet-shaped metal material. The sheet-shaped metal material may be a metal foil, a porous metal, an etched metal, etc. The metal material may be copper, a copper alloy, nickel, stainless steel, etc.

[0067] The negative electrode current collector is a generally disk-shaped metal plate. The material of the negative electrode current collector is, for example, copper, copper alloy, nickel, stainless steel, etc. The material of the negative electrode current collector may be the same as the material of the negative electrode current collector.

[0068] The non-graphitizable carbon may have a (002) plane spacing (i.e., the spacing between carbon layers) d002 of 3.8 Å or more measured by X-ray diffraction. The theoretical capacity of the non-graphitizable carbon is preferably, for example, 150 mAh / g or more. By using the non-graphitizable carbon, it becomes easier to obtain a negative electrode having a small low-temperature DCR and small expansion and contraction due to charging and discharging. The non-graphitizable carbon preferably accounts for 50% by mass or more, further 80% by mass or more, and further 95% by mass or more of the negative electrode active material. In addition, the non-graphitizable carbon preferably accounts for 40% by mass or more, further 70% by mass or more, and further 90% by mass or more of the negative electrode mixture layer.

[0069] As the negative electrode active material, non-graphitizable carbon and a material other than non-graphitizable carbon may be used in combination. Examples of materials other than non-graphitizable carbon that can be used as the negative electrode active material include graphitizable carbon (soft carbon), graphite (natural graphite, artificial graphite, etc.), lithium titanium oxide (spinel type lithium titanium oxide, etc.), silicon oxide, silicon alloy, tin oxide, tin alloy, etc.

[0070] From the viewpoints of high packing ability of the negative electrode active material in the negative electrode and easy suppression of side reactions with the electrolyte, the average particle size of the negative electrode active material (particularly non-graphitizable carbon) is preferably 1 μm to 20 μm, and more preferably 2 μm to 15 μm.

[0071] In this specification, the average particle size refers to the volume-based median diameter (D 50 )

[0072] The negative electrode mixture layer contains a negative electrode active material as an essential component, and contains, as optional components, a conductive material, a binder, etc. Examples of the conductive material include carbon black and carbon fiber, and examples of the binder include fluororesin, acrylic resin, rubber material, and cellulose derivatives.

[0073] The negative electrode mixture layer is formed, for example, by mixing a negative electrode active material with a conductive agent, a binder, and the like together with a dispersion medium to prepare a negative electrode mixture slurry, applying the negative electrode mixture slurry to a negative electrode current collector, and then drying the same.

[0074] The negative electrode mixture layer is pre-doped with lithium ions in advance. This reduces the potential of the negative electrode, increasing the potential difference (i.e., voltage) between the positive electrode and the negative electrode, thereby improving the energy density of the electrochemical device. The amount of lithium pre-doped may be, for example, about 50% to 95% of the maximum amount that can be absorbed in the negative electrode mixture layer.

[0075] The capacitance per unit mass of the negative electrode active material may be, for example, 1000 F / g or more. From the viewpoint of increasing the capacity density of the electrochemical device, the capacitance per unit mass of the negative electrode active material may be, for example, 30000 F / g or less. The capacitance per unit mass of the negative electrode active material is usually larger than the capacitance per unit mass of the positive electrode active material, and is, for example, 20 to 800 times the capacitance per unit mass of the positive electrode active material. The capacitance per unit mass of the negative electrode active material can be measured by the following method.

[0076] First, a negative electrode for evaluation is prepared by cutting into a size of 31 mm x 41 mm. A 100 μm thick metallic lithium foil is prepared as a counter electrode for the negative electrode by cutting into a size of 40 mm x 50 mm. The negative electrode mixture layer and the metallic lithium foil are opposed to each other via a 25 μm thick cellulose paper (e.g., product number TF4425) manufactured by Nippon Kodoshi Kogyo Co., Ltd. as a separator to form an electrode body, and the electrode body is immersed in the electrolyte of Example 1 described later to form a cell.

[0077] Charge at a constant current (CC) of 0.5 mA until the cell voltage reaches 0.01 V, then charge at a constant voltage (CV) for 1 hour, and then discharge at 0.5 mA until the cell voltage reaches 1.5 V. Calculate the capacitance per unit mass of the negative electrode active material from the discharge time required for the negative electrode potential to change by 0.1 V from 1 minute after the start of discharge.

[0078] (positive electrode) The positive electrode comprises a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector, and the positive electrode mixture layer contains a positive electrode active material that reversibly dopes anions, and the positive electrode active material is, for example, a carbon material, a conductive polymer, etc. The thickness of the positive electrode mixture layer is, for example, 10 to 300 μm per side of the positive electrode current collector.

[0079] The positive electrode current collector is made of a sheet-shaped metal material. The sheet-shaped metal material may be a metal foil, a porous metal, an etched metal, etc. The metal material may be aluminum, an aluminum alloy, nickel, titanium, etc.

[0080] The positive electrode current collector is a generally disk-shaped metal plate. It is preferable to form a through hole in the center of the positive electrode current collector, which serves as a passage for the non-aqueous electrolyte. The material of the positive electrode current collector is, for example, aluminum, an aluminum alloy, titanium, stainless steel, or the like. The material of the positive electrode current collector may be the same as the material of the positive electrode current collector.

[0081] The carbon material used as the positive electrode active material is preferably a porous carbon material, for example, activated carbon or the carbon material exemplified as the negative electrode active material (e.g., non-graphitizable carbon). Examples of raw materials for activated carbon include wood, coconut shells, coal, pitch, and phenolic resin. The activated carbon is preferably one that has been subjected to an activation treatment.

[0082] The average particle size of the activated carbon is not particularly limited, but is preferably 20 μm or less, and more preferably 3 μm to 15 μm.

[0083] The specific surface area of ​​the positive electrode mixture layer generally reflects the specific surface area of ​​the positive electrode active material. 2 / g or more, 4000m 2 / g or less is sufficient, and 2 / g or more, 3000m 2 / g or less is preferable. The specific surface area of ​​the positive electrode mixture layer is a BET specific surface area determined using a measuring device conforming to JIS Z8830 (e.g., Tristar II3020 manufactured by Shimadzu Corporation). Specifically, the electrochemical device is disassembled, and the positive electrode is removed. Next, the positive electrode is washed with DMC and dried. Thereafter, the positive electrode mixture layer is peeled off from the positive electrode current collector, and about 0.5 g of a sample of the positive electrode mixture layer is taken. Next, the specific surface area of ​​the taken sample is determined according to the measurement method for the specific surface area of ​​the negative electrode mixture layer already described.

[0084] The activated carbon preferably accounts for 50% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more of the positive electrode active material, and more preferably 40% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more of the positive electrode mixture layer.

[0085] The positive electrode mixture layer contains a positive electrode active material as an essential component, and optionally contains a conductive material, a binder, etc. Examples of the conductive material include carbon black and carbon fiber. Examples of the binder include fluororesin, acrylic resin, rubber material, cellulose derivatives, etc.

[0086] The positive electrode mixture layer is formed, for example, by mixing a positive electrode active material with a conductive agent, a binder, and the like together with a dispersion medium to prepare a positive electrode mixture slurry, applying the positive electrode mixture slurry to a positive electrode current collector, and then drying the same.

[0087] The conductive polymer used as the positive electrode active material is preferably a π-conjugated polymer. For example, polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, polypyridine, or a derivative thereof may be used as the π-conjugated polymer. These may be used alone or in combination of two or more. The weight average molecular weight of the conductive polymer is, for example, 1000 to 100000. The derivative of a π-conjugated polymer means a polymer having a basic skeleton of a π-conjugated polymer such as polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, or polypyridine. For example, polythiophene derivatives include poly(3,4-ethylenedioxythiophene) (PEDOT).

[0088] The conductive polymer is formed, for example, by immersing a positive electrode collector having a carbon layer in a reaction solution containing a raw material monomer of the conductive polymer, and electrolytically polymerizing the raw material monomer in the presence of the positive electrode collector. In electrolytic polymerization, the positive electrode collector and the counter electrode are immersed in a reaction solution containing the raw material monomer, and a current is passed between them using the positive electrode collector as the anode. The conductive polymer may be formed by a method other than electrolytic polymerization. For example, the conductive polymer may be formed by chemical polymerization of the raw material monomer. In chemical polymerization, the raw material monomer is polymerized by an oxidizing agent or the like in the presence of the positive electrode collector.

[0089] The raw material monomer used in the electrolytic polymerization or chemical polymerization may be any polymerizable compound capable of producing a conductive polymer by polymerization. The raw material monomer may include an oligomer. Examples of the raw material monomer include aniline, pyrrole, thiophene, furan, thiophene vinylene, pyridine, or derivatives thereof. These may be used alone or in combination of two or more. Among them, aniline is easy to grow on the surface of the carbon layer by electrolytic polymerization.

[0090] The electrolytic polymerization or chemical polymerization can be carried out using a reaction solution containing an anion (dopant). By doping a π-electron conjugated polymer with a dopant, excellent electrical conductivity is exhibited. Examples of the dopant include sulfate ions, nitrate ions, phosphate ions, borate ions, benzenesulfonate ions, naphthalenesulfonate ions, toluenesulfonate ions, methanesulfonate ions, perchlorate ions, tetrafluoroborate ions, hexafluorophosphate ions, and fluorosulfate ions. The dopant may be a polymer ion. Examples of the polymer ion include ions of polyvinylsulfonic acid, polystyrenesulfonic acid, polyallylsulfonic acid, polyacrylicsulfonic acid, polymethacrylic acid, poly(2-acrylamido-2-methylpropanesulfonic acid), polyisoprenesulfonic acid, and polyacrylic acid.

[0091] (Separator) The separator may be a nonwoven fabric made of cellulose fibers, a nonwoven fabric made of glass fibers, a microporous membrane made of polyolefin, a woven fabric or a nonwoven fabric, etc. The thickness of the separator is, for example, 8 to 300 μm, and preferably 8 to 40 μm.

[0092] (electrolyte) The electrolyte has lithium ion conductivity and contains, for example, a lithium salt and a solvent for dissolving the lithium salt. The anion of the lithium salt is reversibly doped and dedoped into the positive electrode. The lithium ion derived from the lithium salt is reversibly absorbed and released into the negative electrode.

[0093] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiFSO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10, LiCl, LiBr, LiI, LiBCl4, LiN(FSO2)2, LiN(CF3SO2)2, etc. These may be used alone or in combination of two or more. Among them, a salt having a fluorine-containing anion is preferred, and it is particularly preferred to use lithium bis(fluorosulfonyl)imide, i.e., LiN(SO2F)2. The concentration of the lithium salt in the electrolyte in the charged state (state of charge (SOC) 90 to 100%) is, for example, 0.2 to 5 mol / L. Hereinafter, LiN(SO2F)2 will be referred to as LiFSI. For example, 80 mass% or more of the lithium salt may be LiFSI.

[0094] The use of LiFSI tends to significantly reduce the rate of increase in low-temperature DCR. LiFSI is believed to have the effect of reducing the deterioration of the positive and negative active materials. Among salts having fluorine-containing anions, the FSI anion is highly stable, so it is unlikely to produce by-products and is believed to contribute to smooth charging and discharging without damaging the surface of the active material. In particular, when increasing the capacity of the positive electrode and the specific surface area of ​​the negative electrode mixture layer, the effect of suppressing deterioration (the effect of suppressing the increase in low-temperature DCR) by using LiFSI, which significantly reduces the impact of by-products on each active material, becomes significant.

[0095] Examples of the solvent that can be used include cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, aliphatic carboxylates such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate, lactones such as γ-butyrolactone and γ-valerolactone, chain ethers such as 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), and ethoxymethoxyethane (EME), cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethyl monoglyme, trimethoxymethane, sulfolane, methyl sulfolane, and 1,3-propane sultone. These may be used alone or in combination of two or more.

[0096] The electrolyte may contain various additives as necessary. For example, unsaturated carbonates such as vinylene carbonate, vinyl ethylene carbonate, and divinyl ethylene carbonate may be added as additives for forming a lithium ion conductive coating on the surface of the negative electrode.

[0097] [Example] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Table 1 shows an outline of the configuration of each device prepared below.

[0098] (Device A1) (1) Preparation of the positive electrode An aluminum foil (positive electrode current collector) having a thickness of 30 μm was prepared. On the other hand, 88 parts by mass of activated carbon (average particle size 5.5 μm) as a positive electrode active material, 6 parts by mass of polytetrafluoroethylene as a binder, and 6 parts by mass of acetylene black as a conductive material were dispersed in water to prepare a positive electrode mixture slurry. The obtained positive electrode mixture slurry was applied to both sides of an aluminum foil, and the coating was dried and rolled to form a positive electrode mixture layer, thereby obtaining a positive electrode. A positive electrode current collector exposed portion having a width of 10 mm was formed at the end along the longitudinal direction of the positive electrode current collector.

[0099] The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 3.7 mg / cm 2 The capacitance of the positive electrode mixture layer is 90 F / g, and the BET specific surface area of ​​the positive electrode mixture layer is 1700 m 2 / g.

[0100] (2) Preparation of the negative electrode A copper foil (negative electrode current collector) having a thickness of 10 μm was prepared. On the other hand, 97 parts by mass of non-graphitizable carbon (average particle size 5 μm), 1 part by mass of carboxycellulose, and 2 parts by mass of styrene butadiene rubber were dispersed in water to prepare a negative electrode mixture slurry. The obtained negative electrode mixture slurry was applied to both sides of the copper foil, and the coating was dried and rolled to form a negative electrode mixture layer, thereby obtaining a negative electrode.

[0101] The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 3.2 mg / cm 2 (Therefore, the Mp / Mn ratio is 1.1), the capacitance of the negative electrode mixture layer is 5000 F / g, and the BET specific surface area of ​​the negative electrode mixture layer is 10 m 2 / g.

[0102] Thereafter, a thin film of metallic lithium for pre-doping was formed on the entire surface of the negative electrode mixture layer by vacuum deposition. The amount of lithium to be pre-doped was set so that the negative electrode potential in the non-aqueous electrolyte after pre-doping was 0.2 V or less relative to metallic lithium.

[0103] The chamber of the device was then purged with carbon dioxide to create a carbon dioxide gas atmosphere, forming a first layer containing lithium carbonate on the surface of the negative electrode mixture layer. The dew point of the carbon dioxide gas atmosphere was -40°C, the mole fraction of carbon dioxide was 100%, and the pressure in the chamber was 1 atmosphere (1.01 × 10 5 The pressure in the carbon dioxide gas atmosphere was 1 atm. The temperature of the negative electrode exposed to the carbon dioxide gas atmosphere was 25°C. The time for which the negative electrode was exposed to the carbon dioxide gas atmosphere was 22 hours. The first layer did not substantially contain F (or LiF).

[0104] (3) Preparation of the electrode body The positive and negative electrodes were wound in a columnar shape with a cellulose nonwoven separator (thickness 25 μm) in between to form an electrode body. At this time, the exposed part of the positive electrode current collector was protruding from one end face of the wound body, and the exposed part of the negative electrode current collector was protruding from the other end face of the electrode body. A disk-shaped positive electrode current collector plate and a disk-shaped negative electrode current collector plate were welded to the exposed part of the positive electrode current collector and the exposed part of the negative electrode current collector, respectively.

[0105] (4) Preparation of non-aqueous electrolyte A solvent was prepared by adding 0.2 mass% of vinylene carbonate to a mixture of propylene carbonate and dimethyl carbonate in a volume ratio of 1:1. A non-aqueous electrolyte was prepared by dissolving LiFSI as a lithium salt in the obtained solvent at a concentration of 1.2 mol / L.

[0106] (5) Assembly of electrochemical devices The electrode assembly was placed in a bottomed cell case with an opening, a tab lead connected to the positive current collector was connected to the inner surface of a sealing plate, and a negative current collector was welded to the inner bottom surface of the cell case. After placing a non-aqueous electrolyte in the cell case, the opening of the cell case was sealed with a sealing plate to assemble an electrochemical device as shown in Figure 1.

[0107] Thereafter, aging was performed at 60° C. while a charging voltage of 3.8 V was applied between the terminals of the positive electrode and the negative electrode to complete pre-doping of lithium ions into the negative electrode.

[0108] (6) Evaluation [Rating 1] <XPS analysis of the first layer> The surface of the negative electrode mixture layer after exposure to the carbon dioxide gas atmosphere was analyzed by XPS for C1s spectrum, O1s spectrum, and Li1s spectrum. An X-ray photoelectron spectrometer (product name: Model 5600, manufactured by ULVAC-PHI, Inc.) was used for the analysis. The measurement conditions are as follows:

[0109] X-ray source: Al-mono (1486.6eV) 14kV / 200W Measurement diameter: 800μmφ Photoelectron take-off angle: 45° Etching conditions: Acceleration voltage 3 kV, etching rate approximately 3.1 nm / min (SiO2 equivalent), raster area 3.1 mm x 3.4 mm

[0110] Analysis of the C1s spectrum, O1s spectrum, and Li1s spectrum confirmed that the thickness of the first layer was approximately 18 nm. Specifically, peaks such as C-C bonds, which are assumed to be impurity carbon, were observed on the outermost surface, but they rapidly decreased at a depth of about 1 to 2 nm from the first layer. Meanwhile, the first peak attributed to C=O bonds was observed from the outermost surface to a depth of 18 nm in the surface layer. A peak attributed to Li-O bonds was also observed from a depth of about 18 nm. Furthermore, the constant presence of Li was confirmed from the outermost surface to a depth of 18 nm in the surface layer. No peaks attributed to LiF were observed.

[0111] [Rating 2] When the surface of the negative electrode mixture layer of the negative electrode removed from the electrochemical device was analyzed by XPS in the same manner as above, it was confirmed that a 10 nm thick SEI coating (second layer) was formed, which had a different composition from the first layer and was distinct from the first layer. In addition, a peak attributed to LiF was observed.

[0112] [Rating 3] (Measurement of the capacitance of electrochemical devices) Immediately after aging, the electrochemical device was subjected to a current of 2 mA / cm per positive electrode area in a -30°C environment until the voltage reached 3.8 V. 2After constant current charging at a current density of 3.8 V, the battery was charged at 2 mA / cm per positive electrode area for 10 minutes at −30° C. until the voltage reached 2.2 V. 2 A constant current discharge was performed at a current density of 1000 mA / s. In the above discharge, the time t (sec) required for the voltage to drop from 3.3 V to 3.0 V was measured. Using the measured time t, the initial capacity C1 of the electrochemical device was calculated according to the following formula (A).

[0113] Capacity C1=Id×t / V (A)

[0114] In the formula (A), Id is the current value during discharge (current density per positive electrode area: 2 mA / cm 2 × positive electrode area), and V is the value obtained by subtracting 3.0 V from 3.3 V (0.3 V). The evaluation results are shown in Table 2.

[0115] (Measurement of the internal resistance of electrochemical devices) Next, using the discharge curve (vertical axis: discharge voltage, horizontal axis: discharge time) obtained from the above discharge, a linear approximation line was calculated for the range of 0.5 to 2 seconds after the start of discharge of the discharge curve, and the voltage VS at the intercept of the approximation line was calculated. The value (V0-VS) obtained by subtracting the voltage VS from the voltage V0 at the start of discharge (0 seconds after the start of discharge) was calculated as ΔV. ΔV (V) and the current value during discharge (current density per positive electrode area: 2 mA / cm 2 × positive electrode area) according to the following formula (B), the internal resistance (DCR) R1 (Ω) of the electrochemical device was calculated. The evaluation results are shown in Table 2.

[0116] Internal resistance R1=ΔV / Id (B)

[0117] (Float Testing of Electrochemical Devices) Next, a float test was performed in which the electrochemical device was held in an 85°C environment for 1000 hours with a constant voltage of 3.8V applied, and the low-temperature DCR was then measured in the same manner, and the low-temperature DCR increase rate was calculated from the difference (ΔDCR) between the initial low-temperature DCR and that after repeated charging and discharging. The evaluation results are shown in Table 2.

[0118] (Devices A2 to A7) Devices A2 to A7 were fabricated and evaluated in the same manner as Device A1, except that Mp and Mn were changed as follows to change the Mp / Mn ratio as shown in Table 1. The results are shown in Table 2.

[0119] (Device A2) The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 3.0 mg / cm 2 The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 4.2 mg / cm 2 (Therefore, the Mp / Mn ratio was set to 0.7).

[0120] (Device A3) The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 3.9 mg / cm 2 The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 2.8 mg / cm 2 (Therefore, the Mp / Mn ratio was set to 1.4).

[0121] (Device A4) The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 4.1 mg / cm 2 The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 2.6 mg / cm 2 (Therefore, the Mp / Mn ratio was set to 1.6).

[0122] (Device A5) The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 4.2 mg / cm 2 The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 2.3 mg / cm 2 (Therefore, the Mp / Mn ratio was set to 1.8).

[0123] (Device A6) The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 4.5 mg / cm 2 The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 1.8 mg / cm 2 (Therefore, the Mp / Mn ratio was set to 2.5).

[0124] (Device A7) The mass Mp of the positive electrode active material supported on a unit area of ​​the positive electrode is 4.8 mg / cm 2 The mass Mn of the negative electrode active material supported on a unit area of ​​the negative electrode is 1.3 mg / cm 2 (Therefore, the Mp / Mn ratio was set to 3.7).

[0125] (Devices B1 to B7) Devices B1 to B7 were assembled and evaluated in the same manner as Device A1, except that the Mp / Mn ratio was fixed at 1.6 and the specific surface area of ​​the negative electrode mixture layer was changed as shown in Table 1. The results are shown in Table 2. The specific surface area of ​​the negative electrode mixture layer was changed by changing the specific surface area of ​​the non-graphitizable carbon.

[0126] (Devices C1 to C5) The Mp / Mn ratio was fixed at 1.6, and the specific surface area of ​​the negative electrode mixture layer was set to 50 m 2 Devices C1 to C5 were assembled and evaluated in the same manner as Device A1, except that the capacitance was fixed at 1000 nm / g and the thickness of the first layer was changed as shown in Table 1. The results are shown in Table 2. The thickness of the first layer was changed by changing the time for which the negative electrode was exposed to a carbon dioxide gas atmosphere. However, in Device C1, the chamber was not purged with carbon dioxide after the deposition of metallic lithium on the negative electrode mixture layer. Therefore, the first layer was not formed on the negative electrode of Device C1.

[0127] (Device D1) Device D1 was fabricated and evaluated in the same manner as Device A1, except that graphite (average particle size 7 μm) was used as the negative electrode active material instead of non-graphitizable carbon and the Mp / Mn ratio was set to 1.6. The results are shown in Table 2.

[0128] (Device D2) Graphite (average particle size 7 μm) was used as the negative electrode active material instead of non-graphitizable carbon, and the Mp / Mn ratio was set to 1.6. Furthermore, the specific surface area of ​​the negative electrode mixture layer was set to 50 m 2 Device D2 was assembled and evaluated in the same manner as Device A1, except that the capacitance was changed to / g. The results are shown in Table 2.

[0129] (Device D3) Device D3 was assembled and evaluated in the same manner as Device D2, except that the chamber was not purged with carbon dioxide after deposition of metallic lithium on the negative electrode mixture layer. Therefore, the first layer was not formed on the negative electrode of Device D3. The results are shown in Table 2.

[0130] (Device E1) The Mp / Mn ratio was set to 1.6, and the specific surface area of ​​the negative electrode mixture layer was set to 50 m 2 Device E1 was fabricated and evaluated in the same manner as Device A1, except that the ZnO content was 1.0 / g and LiPF6 was used instead of LiFSI as the lithium salt of the electrolyte. The results are shown in Table 2.

[0131] (Device E2) The Mp / Mn ratio is set to 0.7, and the specific surface area of ​​the negative electrode mixture layer is set to 50 m 2 Device E2 was fabricated and evaluated in the same manner as Device A2, except that the ZnO content was 1.0 / g and LiPF6 was used instead of LiFSI as the lithium salt of the electrolyte. The results are shown in Table 2.

[0132] In Table 1, "HC" stands for "non-graphitizable carbon (hard carbon)." In Table 2, the evaluation results are shown as indexes with the evaluation result of device D1 set at 100. The higher the low-temperature capacitance, the more desirable it is, and the lower the low-temperature DCR and DCR increase rate, the more desirable it is.

[0133] [Table 1]

[0134] [Table 2]

[0135] Comparing Devices A1 to A7, it can be seen that the higher the Mp / Mn ratio, the higher the low-temperature capacitance. However, when considering the balance with the low-temperature DCR, it is clear that the Mp / Mn ratio is preferably in the range of 1.1 to 2.5, and more preferably 1.4 to 1.8.

[0136] A comparison of Devices B1 to B7 reveals that the larger the specific surface area of ​​the negative electrode mixture layer, the smaller the low-temperature DCR becomes, while the larger the DCR increase rate becomes. Considering the balance between the low-temperature DCR and the DCR increase rate, the specific surface area of ​​the negative electrode mixture layer is 10 to 70 m 2 / g, and even 25~50m 2 It can be seen that / g is desirable.

[0137] Comparing devices C1 to C5, it can be seen that even when the specific surface area of ​​the negative electrode mixture layer is considerably large, the DCR increase rate is significantly reduced by providing the first layer. This is believed to be because the formation of the first layer stabilizes the state of the second layer during repeated charging and discharging, improving the reliability of the negative electrode. It can also be seen that, as long as the thickness of the first layer is not extremely large, a significant effect can be obtained even if the thickness of the second layer is small.

[0138] In addition, it can be seen that it is difficult to reduce the low-temperature DCR and the DCR increase rate in Devices D1 to D3 because graphite is used as the negative electrode active material. In addition, it can be seen from the comparison between Devices C3 and E1 that LiFSI is effective as a lithium salt in the electrolyte. On the other hand, it can be seen from the comparison between Devices A2 and E2 that LiFSI has no advantage when the Mp / Mn ratio is less than 1.1, but that LiFSI becomes advantageous when the Mp / Mn ratio is increased. [Industrial Applicability]

[0139] The electrochemical device according to the present invention is suitable for use in vehicles, for example. [Explanation of symbols]

[0140] 100: Electrode body 10: Positive electrode 11x: Positive electrode current collector exposed part 13: Positive current collector 15: Tabreed 20: Negative electrode 21x: Negative electrode current collector exposed part 23: Negative electrode current collector 30: Separator 200: Electrochemical devices 210: Cell case 220: Sealing board 221: Gasket

Claims

1. A positive electrode, a negative electrode, and a lithium ion conductive electrolyte, The positive electrode includes a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector, the positive electrode mixture layer contains a positive electrode active material that is reversibly doped with anions, The negative electrode includes a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer includes a negative electrode active material that is reversibly doped with lithium ions, The negative electrode active material contains non-graphitizable carbon, the specific surface area of ​​the negative electrode mixture layer is 10 m 2 / g or more and 70 m 2 / g or less; a ratio Mp / Mn of a mass Mp of the positive electrode active material supported per unit area of ​​the positive electrode to a mass Mn of the negative electrode active material supported per unit area of ​​the negative electrode is 1.1 or more and 2.5 or less.

2. 2. The electrochemical device according to claim 1, wherein the ratio Mp / Mn is 1.4 or more and 1.8 or less.

3. The specific surface area of ​​the negative electrode mixture layer is 25 m 2 / g or more, 50m 2 The electrochemical device according to claim 1 or 2, wherein the surface area of ​​the electrochemical device is 0.1 μm or less.

4. 4. The electrochemical device according to claim 1, wherein a surface layer portion of the negative electrode mixture layer has a first layer containing lithium carbonate.

5. a surface layer portion of the negative electrode mixture layer has a second layer including a solid electrolyte, The electrochemical device according to claim 4 , wherein at least a portion of the second layer covers at least a portion of a surface of the negative electrode mixture layer via the first layer.

6. the second layer contains lithium carbonate; The electrochemical device according to claim 5 , wherein a content of the lithium carbonate contained in the second layer is less than a content of the lithium carbonate contained in the first layer.

7. When the first layer is measured by X-ray photoelectron spectroscopy, a substantial F1s peak attributable to a LiF bond is not observed; 7. The electrochemical device according to claim 5, wherein when the second layer is measured by X-ray photoelectron spectroscopy, a substantial F1s peak attributable to a LiF bond is observed.

8. The electrochemical device according to any one of claims 4 to 7, wherein the first layer has a thickness of 1 nm or more and 50 nm or less.

9. The lithium ion conductive electrolyte is lithium bis(fluorosulfonyl)imide: LiN(SO 2 F) 2 The electrochemical device according to any one of claims 1 to 8, comprising:

10. A positive electrode, a negative electrode, and a lithium ion conductive electrolyte, The positive electrode includes a positive electrode current collector and a positive electrode mixture layer supported on the positive electrode current collector, the positive electrode mixture layer contains a positive electrode active material that is reversibly doped with anions, The negative electrode includes a negative electrode current collector and a negative electrode mixture layer supported on the negative electrode current collector, the negative electrode mixture layer includes a negative electrode active material that is reversibly doped with lithium ions, The negative electrode active material contains non-graphitizable carbon, a surface layer portion of the negative electrode mixture layer has a first layer containing lithium carbonate, a ratio Mp / Mn of a mass Mp of the positive electrode active material supported per unit area of ​​the positive electrode to a mass Mn of the negative electrode active material supported per unit area of ​​the negative electrode is 1.1 or more and 2.5 or less.

Citation Information

Patent Citations

  • JP1974071729A

  • Lithium-ion capacitor

    JP2006310412A

  • Electricity storage element

    JP2016186886A

  • Lithium ion capacitor

    JP2018014435A

  • Power storage element

    JP2018120829A